Theoretical-Pragmatic approaches to women's autonomy: a space under construction - Hidalgo Redondo, Giselle (2024)
his article focuses on women's autonomy as a human right and foundation for gender equality. The aim is to identify the articulations that incorporate the concept of women’s autonomy. The research considered the theoretical approaches present in Patriarchy and Accumulation on a World Scale (2019), by María Mies, and Claves feministas para mis socias de la vida (2015), by Marcela Lagarde as well as the approach taken by the Gender Equality Observatory for Latin America and the Caribbean, an instance of the Economic Commission for Latin America and the Caribbean. The authors concluded that the scope of autonomy requires the support of the international community to continue promoting the creation of public policies that encourage respect for human rights, guarantee gender equality, and foster more equitable forms in the distribution of wealth and power for women and men equally.